Status of postgraduate training in the livestock sector in West and Central Africa and priorities for ILRI’s support - Traoré, A. (International Livestock Research Institute, 2009)
Research-based capacity strengthening is one of the priority activities of the International Livestock Research Institute (ILRI). The mission of ILRI’s Capacity Strengthening Unit (CaSt) is to strengthen the capacity of the livestock research and development community to contribute to the overall mandate of ILRI in achieving livestock-mediated poverty alleviation. The purpose of Cast is to strengthen the capacity of ILRI’s partners to apply their skills and resources to accomplish their goals, satisfy stakeholders’ needs and improve performance and impact. The overall purpose of this study was to identify areas for collaborative action to build the capacity of learning institutes in the region. Given the different stages of development of the various universities, it may also be necessary to initiate some carefully selected national level activities to complement the regional undertakings. ILRI will make every effort to facilitate and support the national and regional initiatives in strengthening the capacities of the universities especially the postgraduate research and training in the region.